The Design of Directional Coupler for ECRH System - Dajun Wu; Fukun Liu; Xiaojie Wang; Handong Xu; Liyuan Zhang; Weiye Xu; Yunying Tang; Jian Wang (IEEE Access, 2017)
A study of coupling characteristic between circular corrugated waveguide and rectangular smooth waveguide has been presented in this paper, which aims to develop a directional coupler integrated into a miter bend for an electron cyclotron resonance heating system on EAST. The performances of the several aperture array distributions are analyzed based on the aperture diffraction theory in detail. The broadband, good in-band coupling flatness, and excellent directivity are achieved by using the proposed novel aperture array on the mirror surface. For verification purpose, a prototype of the directional coupler has been designed and fabricated.